2020
DOI: 10.3390/pharmaceutics12020130
|View full text |Cite
|
Sign up to set email alerts
|

Self-Microemulsifying Drug Delivery System of Phillygenin: Formulation Development, Characterization and Pharmacokinetic Evaluation

Abstract: Phillygenin, as an active ingredient of Forsythia suspensa, possesses a wide range of biological and pharmacological activity. However, its development and application are restricted due to its poor bioavailability and low solubility. Our work aimed to develop a self-microemulsifying drug delivery system to improve the oral bioavailability of phillygenin. The composition of the self-microemulsifying drug delivery system was preliminary screened by the pseudo-ternary phase diagram. Subsequently, the central com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…The TEM image (Fig. 2(B)) shows that the LQ‐SNEDDS was regular sphere with good dispersibility, which agrees with Wang's result 19 . The EE and DL of LQ‐SNEDDS were respectively 91.32% ± 2.39% and 2.44% ± 0.04%, and the result indicated that a large amount of LQ was encapsulated in SNEDDS.…”
Section: Resultssupporting
confidence: 86%
“…The TEM image (Fig. 2(B)) shows that the LQ‐SNEDDS was regular sphere with good dispersibility, which agrees with Wang's result 19 . The EE and DL of LQ‐SNEDDS were respectively 91.32% ± 2.39% and 2.44% ± 0.04%, and the result indicated that a large amount of LQ was encapsulated in SNEDDS.…”
Section: Resultssupporting
confidence: 86%
“…Another CCD strategy was used by Yan and coworkers to examine the similar responses (droplet size, PDI, and dissolution efficiency) toward SMEDDS for β-elemene formulation composing poly (acrylic acid) (PAA) entailed on mesoporous silica nanoparticles (MSNPs). The authors emphasized the use of the PAA/MSNPs loaded in SMEDDS to increase the drug loading and to act as the pH triggers in improving a controlled release behavior in an acidic environment [ 82 ]. Several reports of CCD applications that have been incorporated in SMEDDS are listed in Table 6 .…”
Section: Advantages Of Applying Doe Techniques For the Development Of...mentioning
confidence: 99%
“…Due to the short length of the carbon chain, MCTs directly diffuse through the gastrointestinal tract by the mechanism of passive diffusion into the portal system without undergo any molecular modifications. Lipids enable faster absorption from of the gastrointestinal tract compared to long-chain triglycerides and are preferred due to their greater capacity for drug dissolution and higher resistance to oxidation [16,17]. Triglyceride vegetable oils are well absorbed and digested.…”
Section: Drug Substancementioning
confidence: 99%